Ambipolar conduction in recessed channel Schottky barrier MOSFETs - Chun-Hsing Shih (IEEE Publishing, 2024)
The ambipolar conduction is numerically studied in recessed channel Schottky barrier MOSFET (RC-SBMOS). The results show that the recessed channel structure can alleviate the lateral field penetrations coming from drain electrode. Thus, it is rather insensitive to the variations of drain voltages. However, the parasitic recessed channel leads to a lower on-state driving current. The depth of the recessed channel must be well designed to have good current characteristics in RC-SBMOS. Importantly, the recessed channel structure has only a mild effect on suppressing the off-state ambipolar hole current.